Obtaining Preferences from a Hybrid Learning System to Promote English-Speaking Ability through Focus Group Discussion - Tan Winona Vania Anabel; Debora Chaterin Simanjuntak (Universitas Pendidikan Mandalika, 2022)
In the new normal era, the learning system has changed from online learning to hybrid learning. This learning system is widely applied in many universities. Thus surfacing students and lecturers’ voices is of absolute importance in obtaining preferences for best practices in English language teaching. In the EFL context, speaking fluency is one of the elements of speaking that have many difficulties to be mastered by students. This study was conducted to derive suggestions and preferences for best practices in hybrid learning systems for English-speaking ability through Focus Group Discussion (FGD) method. From the FGD, we draw transcripts, back-to-back translations, field notes and activity artefacts to demonstrate the process of the discussion. The information gathered was examined using thematic analysis and an interpretative description approach. The participants of this study were Non-English majors and English lecturers. The result revealed that college students faced speaking challenges during hybrid learning to hone their speaking fluency. Emerging themes were identified wherein in a hybrid learning system, the lecturer utilized multifaceted learning, digital resources and communication tools to improve students' speaking fluency. As for the implementation, technical support and mental readiness for hybrid learning are the reasons for the possibility of hybrid learning that affects students' speaking fluency.